ANALISIS SELF DETERMINATION SEBAGAI INDIKATOR KEBERHASILAN PROGRAM ANGKATAN 1 TAHUN 2026 UPTD PSRAMPK DINAS SOSIAL PROVINSI SUMATERA SELATAN - Rizky Amaliyah; Salsyah Riski Nabila (Jurnal Edukasi Pengabdian Masyarakat, 2026)
This community service program was implemented in UPTD PSRAMPK, the Social Affairs Office of South Sumatra Province, because several students showed strong motivation in vocational training but still faced challenges in discipline, initiative, and future orientation. The program aimed to strengthen students’ self-determination through psychosocial guidance based on Self-Determination Theory. The method used was participatory psychoeducation conducted in three stages: preparation, implementation, and evaluation, with activities focused on self-awareness, self-confidence, and self-development. The results showed positive changes in students’ ability to recognize their strengths, express opinions more confidently, and develop clearer plans for the future. Overall, the program supported students’ psychological readiness for independent life after rehabilitation. Keywords: future orientation; psychosocial guidance; psychoeducation; self-confidence; self-determination